Preparation of Karam from the mid stem of the Musa acuminata as Nasiyam in the treatment of Nasikapeedam (Nasal polyposis) - Thayalini, T.; Tharshika, S.; Ajanthan, T.; Athavan, V.; Rasalingam, S. (Gampaha Wickramarachchi Ayurveda Institute University of Kelaniya, Sri Lanka, 2017)
In Siddha Medicine, most of the herbs are used in the preparation of Siddha drugs. In ancient times, surgery was carried out by Siddha Physicians using Kara liquids. Nasikapeedam (Nasal polyposis) is one of the common diseases in Siroroga Maruththuvam (diseases of neck and above). Nasiyam (nasal drops) is one of the treatment methods for head disorders. Herbal juices, herbal oils, herbal drugs which are prepared with herbs are used as Nasiyam through nasal cavities. Mid stem of Musa acuminata, dried peel of M. acuminata and peel of ash plantain have been used to prepare Karam in the treatment of Nasikapeedam. Nasal polyposis is a surgical condition, which is related to allergic conditions. In Siddha medicine, Karapirayokam is used to remove the mass from elsewhere. The aim of this study was to prepare the Karam from the mid stem of the M. acuminata used in the treatment of Nasikapeedam. Mid stem of M. acuminata was obtained from the field of banana in Kaithady area. The stem was cut into small pieces and dried under sunshade for 2 weeks. After that, the dried stem was stored in polythene bags. The ash was prepared from the stem by air burning. The obtained ash was weighed in appropriate amount and washed with 50 ml of water. The pH of the supernatant solution was measured using pH paper and was further confirmed by the pH probe. The procedure was repeated for 7 times. The results obtained for pH were as follows; 12.06, 11.78, 11.38, 10.97, 10.78, 10.67, and 10.59. The pH measured was within the acceptable range for external use, and, thus, it can be concluded that the Karam from the M. acuminata could be used in the treatment of Nasikapeedam. Clinical trial should be carried out to determine the efficacy of Karam in the treatment of Nasikapeedam.
Keywords: Nasikapeedam; Karam; Musa acuminata